Sistem Pakar Mendiagnosa Penyakit Tumor Phyllodes Pada Wanita Menggunakan Metode Dempster Shafer - Ratnida Saragih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Expert system is a system that combines human knowledge into a computer designed to mimic the expertise of an expert in solving problems such as those done by experts, and with the existence of an expert system can help doctors get information in diagnosing disease. Phyllodes tumors are rare fibroepithelial malignancy neoplasms and this disease is also quite a step, the incidence is only about 0.3-0.9% of all breast tumors, these tumors appear and continue to grow, while some types of phyllodes tumor disease in the malignant category and benign, mammary cancer, fibroadenoma tumor, mastitis, gynecomastia, paget cancer. By applying the shafer dempster method aims to diagnose phyllodes tumor disease based on phyllodes tumor symptoms, the results of the study are expected to make it easier for doctors to provide diagnostic results accurately, so as to produce results that match the patient's symptoms